(untitled) (Bangladesh Medical Journal, 2019)
Globally tuberculosis (TB) has become the leading cause of death from infectious diseases. Tuberculosis is a chronic infection and a person may suffer from tuberculosis and other chronic medical conditions at the same time. Co-occurrence of multiple chronic conditions in the same individual, known as multimorbidity (MM) is increasing worldwide. This cross-sectional study was carried out from January 2017 to December 2017 to reveal the extent of multimorbidity among tuberculosis cases. A TB case with multimorbidity was defined as TB with multimorbidity (TB-MM) subject. By convenient sampling, 227 tuberculosis cases from 8 Directly Observed Treatment, Short Course (DOTS) centers from Dhaka, Mymensingh and Netrokona districts were enrolled in this study. Among 227 tuberculosis cases 29 (12.8%) cases had multimorbidity (TB-MM subjects). Prevalence of multimorbidity was significantly higher in age group ≥40 years (p<0.001), male cases (p=0.034) and cases who had family income >30000 BDT/month (p=0.001), were currently smoker (p=0.028) and whose BCG scars were not seen (p<0.001). This study recommends that each TB case should be investigated for other chronic conditions to reveal the actual national magnitude of multimorbidity. Bangladesh Med J. 2017 Sep; 46 (3): 74-79